(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
This paper is concerned with the relevance of a Kierkegaardian notion of choice for psychotherapy. Exploration of his ideas, as those also appear in the work of different philosophers and psychotherapists, seem to point to the relational nature of choice, and its quality as an existential given. A discussion of possible influences on Kierkegaard and his work is also presented. Issues relating to practicing psychotherapy ethically are teased out in the process.